Interventions to prevent obesity in Latinx children birth to 6 years globally: a systematic review - Rachel Bleiweiss-Sande; Kara Skelton; Daniel Zaltz; Montserrat Bacardí-Gascón; Arturo Jiménez-Cruz; Sara E Benjamin-Neelon (Cambridge University Press, 2023)
Abstract Objective: To conduct a systematic review of obesity prevention interventions in Latinx children ages birth to 6 years published in any language from 2010-2020. Design: We used PubMed, ERIC, PsycINFO, Scopus, Scientific Electronic Library Online (SciELO) and Google Scholar databases to conduct a search on May 1 2020, January 1 2021 and November 1 2022. We included randomised controlled trials, quasi-experimental studies and non-randomised interventions with a control or comparison group that reported measures of adiposity. Setting: Interventions taking place in the United States, Latin America or the Caribbean. Participants: Latinx children ages birth to 6 years. Results: Of 8601 unique records identified, forty manuscripts about thirty-nine unique studies describing thirty distinct interventions in the United States and nine interventions in Latin America and the Caribbean met our inclusion criteria. Interventions were primarily based in early care and education centres (n 13) or combined home settings, for example home and community (n 7). Randomised interventions taking place in community or home settings were more likely to report significant reductions in adiposity or weight-related outcomes compared to other settings. Using the Cochrane risk of bias tools for randomised and non-randomised studies, we judged thirty-eight randomised trials and nine non-randomised interventions to have a high or unclear risk of bias. Conclusions: The results highlight a need for more rigorous designs and more effective intervention strategies in Latinx children at risk for having overweight and obesity. Registered with the PROSPERO database for systematic reviews under registration number CRD42020161339.